Effects of selective versus non- selective cox-2 inhibition on experimental periodontitis - Moro, Marcella Goetz; Oliveira, Marilia Dantas Dos Santos; Oliveira, Leticia Rodrigues De; Teixeira, Simone Aparecida; Muscará, Marcelo Nicolas; Spolidorio, Luis Carlos [UNESP]; Holzhausen, Marinella (FapUNIFESP (SciELO), 2019)
In the present study we compared the effects of the selective COX-2 inhibitor etoricoxib with those of the classical non-selective NSAID diclofenac on the inflammatory process and alveolar bone loss in an experimental model of periodontitis in rats. Ninety male Holtzman rats (250 g) were randomly sorted into four experimental groups: Sham+CMC and Ligature+CMC (control) groups which received 0.5% carboxymethylcellulose sodium (CMC) solution; Ligature+Diclofenac and Ligature+Etoricoxib groups which received Potassium Diclofenac and Etoricoxib, respectively, suspended in 0.5% CMC (10 mg/kg/day). At 7, 14 and 21 days after placing ligatures in the cervical region of both the lower right and left first molars, the animals were euthanized. At the end of each period, the mandibles were collected for radiographic examination of alveolar bone loss. In addition, alveolar bone and periodontal ligament tissue samples were collected for COX-2 expression analysis and gingival tissues were collected for measurement of PGE2 contents. Animals with ligature-induced periodontal disease showed significant increased COX-2 gene expression at days 7, 14 and 21 (p<0.05) on alveolar bone and periodontal ligament. However, both treatments resulted in significantly reduced alveolar bone loss when compared to the untreated Ligature group (p<0.05), with no statistical difference between Etoricoxib and Diclofenac Potassium groups. This study shows that both drugs were able to reduce alveolar bone loss after periodontal disease induction.
Keywords: Cyclooxygenase inhibitors; Periodontitis; Rats